Design of experiment for improving unbalanced polyethylene terepthalate bottle thickness proble [electronic resource] - Norlia Harudin, 1984- (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2008